Risiko Kontaminasi Bakteriologis Pada Sarana Air Bersih Di Desa Baruh Tabing Kecamatan Banjang - Imam Santoso; Maharso Maharso; Darmiah Darmiah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract: The bacteriological contamination risk of clean water facilities in Desa Baruh Tabing, Banjang Sub district. The Indonesian government as part of the population of the world is committed to achieving the Millennium Development Goals (MDG), particularly in the field of Water Supply and Sanitation (WSS) which lowers the number of people who do not have access to drinking water and basic sanitation by 50% in 2015. However, drinking water coverage in 2010 amounted to 48.8% for the physical. This study aims to determined differences in the bacteriological quality of water is based on the type of water supply system in the Desa Baruh Tabing at Banjang’s Puskesmas working area. Using a cross sectional study design. A sample of 9 pieces of SAB with the sampling method performed Saturation Sampling. The sampling period was done three (3) times in one month on each of clean water facilities to be checked, so the total number of water samples of 27 samples. Analysis used ANOVA test. The results showed no significant difference between the numbers of clean water facilities with p = 0.010 at α = 0.05; bacteriological quality (number of coliform) the highest number is 1,898, while the lowest is zero. For the average value of the highest coliform number 1,898 on Dug wells. While the risk of coliform contamination in water supply facilities in the high category as much as 44.4% and 11.1% very high category. To keep the risk of coliform contamination of the water supply facilities, monitoring is done periodically by the authorities. Keywords: the risk of contamination; bacteriological; clean water facilities